2010
DOI: 10.1292/jvms.10-0158
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Genes Encoding Virulence Determinants and Toxins in Staphylococcus aureus from Bovine Milk in Central Italy

Abstract: ABSTRACT. The aim of this study was to evaluate the genotypic characteristics of Staphylococcus aureus isolates (n=170) from bovine milk collected from seven dairy farms in Italy. On the basis of cultural and biochemical properties and by amplification of the 23S rRNA specific to S. aureus, all isolates were identified as S. aureus. To genotypically characterize S. aureus isolates, genes encoding virulence determinants (nuc, clfA, spa-IgG-binding, spa-X-region, fnbA and fnbB, cap5 and cap8) and staphylococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In another study, Borges et al [17] observed S. aureus in 67% (16/24) of isolates from raw milk. Worldwide, several studies suggest that the S. aureus isolation rates in milk can vary from 13.5% to 64.7% [12] [18] [19]. Furthermore, in the present study, a high frequency of isolation of S. aureus was observed in samples collected directly from bulk tanks.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In another study, Borges et al [17] observed S. aureus in 67% (16/24) of isolates from raw milk. Worldwide, several studies suggest that the S. aureus isolation rates in milk can vary from 13.5% to 64.7% [12] [18] [19]. Furthermore, in the present study, a high frequency of isolation of S. aureus was observed in samples collected directly from bulk tanks.…”
Section: Discussionsupporting
confidence: 51%
“…Staphylococci cultures in 2 mL of TSB medium were used for DNA extraction according to the method described by Fan et al [11]. The isolates were submitted to PCR for detection of virulence factors genes: sea (Staphylococcal enterotoxins type A), seb (Staphylococcal enterotoxins type B), sec (Staphylococcal enterotoxins type C), pvl (Panton-Valentine Leucocidin), clfA (Clumping factor) and spa (IgG-binding region and the X-region of protein A) using primers described by Proietti et al [12]. The primer sequences of the sea, seb, sec, PVL, spa and CflA genes are described in Table 1.…”
Section: Genotypic Characterization To Pathogenic Genesmentioning
confidence: 99%
“…SCC mec typing of MRSA strains was conducted by a multiplex PCR method as previously described [ 13 ]. The presence of the genes that code for Panton-Valentine leukocidin ( lukF-PV/lukS-PV or pvl ), twelve staphylococcal enterotoxins ( sea~see, seg~sej and sem-seo ), two exfoliative toxins ( eta and etb ), four haemolysins ( α-hemolysin, β-hemolysin, δ-hemolysin, and γ-hemolysin ), three biofilm information-related genes ( ica A, ica D and bap ), and the toxic shock syndrome toxin ( tsst- 1) and mec A gene were determined using PCR as previously reported, with some modification [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hence, due to their ability to cause numerous sporadic cases and foodborne disease outbreaks in humans, they have become a significant public health threat [ 10 , 11 , 12 ]. Staphylococcus aureus , on the other hand, produces a variety of potent staphylococcal enterotoxins (SEs), which are resistant to inactivation by gastrointestinal proteases and are consequently responsible for staphylococcal food poisoning [ 10 , 13 ]. Severe gastroenteritis can develop within one to seven hours after the consumption of Staphylococcus aureus contaminated food, leading to diarrhoea, vomiting, and dehydration.…”
Section: Introductionmentioning
confidence: 99%